2014
DOI: 10.1176/appi.ps.201300468
|View full text |Cite
|
Sign up to set email alerts
|

Research and Services Partnerships: Responding to Needs of Clinical Operations Partners: Transferring Implementation Facilitation Knowledge and Skills

Abstract: This column describes a facilitation strategy that incorporates evidence-based implementation knowledge and practice-based wisdom. The authors also describe a partnership between research and clinical operations leaders in the U.S. Department of Veterans Affairs to bridge the gap between implementation knowledge and its use. The initial product of the partnership, the Implementation Facilitation Training Manual: Using External and Internal Facilitation to Improve Care in the Veterans Health Administration, is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 8 publications
0
35
0
Order By: Relevance
“…In fact, VA leadership has already adopted this facilitation strategy to support implementation of PC-MHI, as well as other policy-mandated evidence-based innovations, at facilities across VA that struggle to implement new programs [9, 10, 15, 75]. Based on experiences of facilitators in this study, we developed IF training materials and the external expert facilitator (JEK) and one of the internal regional facilitators have been training clinical operations personnel in these methods [76, 77]. They have also trained other researchers in the application of implementation facilitation.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, VA leadership has already adopted this facilitation strategy to support implementation of PC-MHI, as well as other policy-mandated evidence-based innovations, at facilities across VA that struggle to implement new programs [9, 10, 15, 75]. Based on experiences of facilitators in this study, we developed IF training materials and the external expert facilitator (JEK) and one of the internal regional facilitators have been training clinical operations personnel in these methods [76, 77]. They have also trained other researchers in the application of implementation facilitation.…”
Section: Discussionmentioning
confidence: 99%
“…VA leadership has already adopted IF nationally and has expanded it beyond PC-MHI to other clinical initiatives, with our facilitators training clinical operations personnel and developing resources. 24,34,35 Although this work was conducted within VA, the IF strategy could be applied in other healthcare systems willing to provide resources dedicated to innovative implementation.…”
Section: Discussionmentioning
confidence: 99%
“…This manuscript describes the development, implementation, and evaluation of a highly partnered IF Training Program that addresses this gap. The IF Training Program, which was initiated to address healthcare leaders' needs within a single large healthcare system (VHA) [34], has developed into a robust program that continues to train growing numbers of implementation practitioners and researchers inside and outside of the healthcare system for which it was originally developed.…”
Section: Discussionmentioning
confidence: 99%
“…In response to this request, we began collaborative discussions with them about ways to meet their needs, resources they could contribute to the effort, and future partnership activities. Literature and our own experiences suggested that our partners needed information on IF that was relevant, timely, and written in nonacademic language [34,35]. Subsequently, we developed an IF Training Manual to serve as source material for a training workshop on IF and as a reference for those receiving ongoing mentoring in IF [36].…”
Section: Initial Development Of the Implementation Facilitation Trainmentioning
confidence: 99%